Characteristics of Compost from Straw and Fisheries Waste: A Comparative Analysis of Different Decomposers - Azizah, Isnaniar Rahmatul; Susilowati, Lolita Endang; Jaya, Dori Kusuma; Arifin, Zainal (International Journal of Technology, Food and Agriculture, 2024)
The objective of this research was to assess the efficacy of three different decomposers in producing compost of high quality that meets the compost maturity standards (SNI 19-7030-2004). The experimental study was conducted with three treatments, each replicated five times, resulting in a total of fifteen composting holes. The research was conducted in South Batu Kuta Village, Narmada District, West Lombok Regency, from October to December 2019. The treatments included D1 (EM4 decomposer), D2 (Promi decomposer), and D3 (Phosphate Solubilizing Bacteria (PSB) decomposer). Various parameters, such as color, smell, temperature, pH, C-Organic, Total N, and C:N ratio, were assessed. The findings demonstrated that all three decomposers effectively decomposed the compost, yielding a high-quality product suitable for various plant applications. The compost produced by EM4, Promi, and PSB decomposers exhibited characteristics such as a blackish color, soil-like smell, a temperature ranging from 29.2°C to 29.8°C, a pH ranging from 6.83 to 6.87, organic carbon content ranging from 12.87% to 14.73%, total nitrogen content ranging from 0.83% to 0.87%, and a C/N ratio ranging from 14.35% to 14.60%. These results align with the compost maturity standards specified in SNI 19-7030-2004.